ChemInform Abstract: Improved Negishi Cross‐Coupling Reactions of an Organozinc Reagent Derived from L‐Aspartic Acid with Monohalopyridines. Issue 27 (8th July 2014) - Usuki, Toyonobu; Yanuma, Hiroto; Hayashi, Takahiro; Yamada, Haruka; Suzuki, Noriyuki; Masuyama, Yoshiro
Abstract The palladium‐catalyzed Negishi cross‐coupling reaction is improved by using Pd2(dba)3 and P(2‐furyl)3 as the catalyst system and by removing both the undesired Zn(II) species and the insoluble Zn metal from the activated organozinc reagent via centrifugation.